Urban Farming Dengan Sistem Hidroponik NFT (Nutrient Film Technique) Dipengaruhi Kemiringan Talang dan Debit Air pada Produksi Tanaman Pakcoy (Brassica rapa chinensis) - Puspitahati Puspitahati; Rindy Andini; Rahmad HP (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Puspitahati P, Andini R, HP Rahmad. 2021. Urban farming with NFT (Nutrient Film Technique) hydroponic influenced by gutter slope and water discharge on pakcoy (Brassica rapa chinensis) production. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 835-843. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). In the era of a pandemic that requires us to reduce mobility outside the home, people lose their activities and jobs. One alternative for activities in the pandemic era is growing vegetables using a hydroponic farming system. The hydroponic system is urban farming which is one of the extensification of agriculture and can prosper the community in the pandemic era. This study aims to determine the production of pakcoy plants using several slopes of gutters and water discharge in the NFT hydroponic system. The research method used was the Split Plot Design with two research factors, namely the water discharge (Q) as the main plot consisting of two treatment levels and the slope of the Talang (T) as a subplot consisting of three treatment levels with the combination treatments repeated three times. The parameters of this study were plant height, number of leaves, fresh weight, and plant productivity. The conclusion of the study was that the water discharge and the slope of the gutters had a significant effect on plant height, number of leaves and fresh weight of pakcoy plants. Pakcoy plant productivity was the greatest at 6% gutter slope with a water flow rate of 0.5 l/minute, which is 0.463 kg/m2. While the smallest was at 4% gutter slope with a water discharge of 1.3 l/minute 0.354 kg/m2. The growth of pakcoy plants at 6% gutter slope and 0.5 l/minute water flow tends to be better when compared to 4%, 6% and 8% gutter slopes and 1.3 l/minute water flow.